Kepribadian Sulit dan Kegagalan Kuliah Mahasiswa - Tukina, Tukina (Bina Nusantara University, 2011)
Student life in university has many dynamics. One of the important and basic problems that could threat successful learning in the university is difficult personality of the student. The article discusses many students failed in university because of having difficult personality. Therefore, handling difficult personality among students must be done as soon as possible. Based on analysis of literature study, efforts in handling difficult personality must be done through the exact education purpose. This is to be thought many parts, including academic community in the university to create students having knowledge and technology and also good characteristic.